Dampak Implementasi Kurikulum Merdeka. terhadap Literasi Siswa Sekolah Dasar di UPTD SDN 05 Sarilamak Kec.Harau Kabupaten Limapuluh Kota. - Hidayati Alya; Aminah Ganda Sari; Adrias Adrias; Fadila Suciana (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
This study was motivated by the need to understand the impact of changing the education curriculum on elementary school students. Curriculum changes often pose challenges in their implementation, especially in terms of literacy in elementary school students. In addition, there are factors that influence student literacy such as the change from the 2013 curriculum to the independent curriculum, lack of support and attention from parents to students, and support from student schools. The purpose of this study was to identify the impact of changing the education curriculum on elementary school students. The research method used is qualitative descriptive with a literature study design. The literature review was conducted by examining information collected from primary and secondary data sources, including citing relevant references. The results of the study indicate that the implementation of the independent curriculum also raises concerns about students' basic skills, especially in terms of reading because many students in Indonesia have difficulty reading, which can have a negative impact on their learning achievement in the future. Therefore, the results of this study are expected to contribute to the understanding and implementation of the independent curriculum in children's literacy